Near and Intermediate Field Evolution of A Negatively Buoyant Jet - Raed Bashitialshaaer,; Kenneth M. Persson, (Journal of Basic & Applied Sciences, 2012)
In this study, a mathematical model was developed to simulate the jet and plume behavior in order to determine the optimum discharge conditions for different scenarios. The model was divided into two sub-models, describing respectively the near and intermediate field properties of the discharge for different inclinations and bottom slope. The lateral spreading and electrical conductivity was also described through a generalization of measured data. The predictions of the model were compared with experimental data collected in lab as well as results obtained with a commercial software CORMIX. A Matlab code was also developed describing the lateral spreading and centerline dilution of buoyant jet and plumes for near and intermediate field was developed. The model produces results in acceptable agreement with data and observations, even though some improvements should be made in order to give the correct weight to the bottom slope parameter and to reduce the need for user calibration. This study has limited result for only 16% bottom slope and 30 degrees inclination. Concentration was improved with the bottom slope by 10% than the horizontal bottoms and improved by about 40% with bottom slope together with inclination of 30 degrees.